Analysis of Availability of Case-Based Reasoning Approaches on Physics Textbooks Class X Semester 1 - Nabila Melia Hanum; Fanny Rahmatina Rahim; Silvi Yulia Sari (Universitas Lambung Mangkurat, 2023)
Learning is strengthened by using an approach to learning. In the 2013 curriculum, it is recommended to use an approach to learning, one of which is the Case-Based Reasoning (CBR) approach. One approach similar to the current process standards is the CBR approach, which helps teachers provide more student involvement in learning activities. There are many physics textbooks that many publishers have circulated, so It is vital to investigate whether or not these books have provided a CBR approach to learning to improve reasoning skills and higher-order thinking as suggested in the 2013 curriculum. This research was done to analyze the CBR approach. CBR is in a physics textbook for class X, semester 1, at Public High Schools in the City of Padang. The research carried out included descriptive research using a qualitative approach. The research population consisted of all physics textbooks for class X high school published in Indonesia and used in the city of Padang. The research samples were three Physics textbooks for Class X High School Semester 1: ER, IP, and TS. The research results showed that no CBR approach was found in the three physics textbooks analyzed. Hence, we concluded that no textbooks are currently available that provide a CBR approach.